Insecticidal Serralysin of Serratia marcescens Is Detoxified in M3 Midgut Region of Riptortus pedestris - Lee, Junbeom; Lee, Dae-Weon (Frontiers in Microbiology, 2022)
Riptortus pedestris insect indiscriminately acquires not only the symbiotic bacterium Burkholderia insecticola, but also entomopathogens that are abundant in the soil via feeding. However, it is unclear how the host insect survives oral infections of entomopathogens. A previous study suggested that serralysin, a potent virulence factor produced by Serratia marcescens, suppresses cellular immunity by degrading adhesion molecules, thereby contributing to bacterial pathogenesis. Here, we observed that S. marcescens orally administered to R. pedestris stably colonized the insect midgut, while not exhibiting insecticidal activity. Additionally, oral infection with S. marcescens did not affect the host growth or fitness. When co-incubated with the midgut lysates of R. pedestris, serralysin was remarkably degraded. The detoxification activity against serralysin was enhanced in the midgut extract of gut symbiont-colonizing insects. The mRNA expression levels of serralysin genes were negligible in M3-colonizing S. marcescens. M3-colonizing S. marcescens did not produce serralysin toxin. Immunoblot analyses revealed that serralysin was not detected in the M3 midgut region. The findings of our study suggest that orally-infected S. marcescens lose entomopathogenicity through host-derived degrading factors and suppression of serralysin.